استخدام مؤشر الجودة (NSFWQI) لتحديد نوعية مياه بحيرة سد الباسل في طرطوس. - سلمان, هناء; جناد, هيثم; كباس, ريتا (Latakia University Journal -Engineering Sciences Series, 2018)
This research aims to evaluate validity of AL- Bassel Dam Lake for the purposes of drinking by using Water quality indices, to achieve this aim, PHysical, chemical and bacterial measurements in four locations of the lake (S1, S2, S3, S4) were conducted periodically. The work continued to conduct tests for full hydrological cycle as of January (2016) until December (2016).The parameters measured are the following: Temperature Changes of water, PH- Value, Dissolved Oxygen, Biochemical Oxygen Demand, NO3 -, Total Suspended Solid, Turbidity, PO4-3and Fecal Coliform.Results were represented diagrammatically and then the resulting values were compared with the allowable values the potable water according to the Syrian Specifications Standards no (45) (2007). Many of parameters have exceeded the allowable limits specifically. In accordance with the results that have been obtained, the lake has been classified according to the international quality index (NSFWQI) and was at the grade (C) in the sampling sites (S1, S2, S3) and the description was (Medium), and was at the grade (D) in the sampling site (S4) and the description was (Bad). Consequently, the water of the lake was not good for drinking and needs treatment. يهدف البحث إلى تقييم صلاحيّة بحيرة سدّ الباسل للشرب باستخدام دلائل جودة المياه، وللوصول إلى هذا الهدف كان من الضروري إجراء تحاليل دوريّة فيزيائيّة، كيميائيّة وجرثوميّة لمياه البحيرة، في أربعة مواقع (S1-S2-S3- S4)، لدورة هيدرولوجيّة كاملة ابتداءً من كانون الثاني (2016) حتّى كانون الأول .(2016)البارامترات التي تمّ قياسها هي الآتية: تغيّرات درجة حرارة المياه، الرقم الهيدروجيني، الأوكسجين المنحل، الطلب الحيوي للأوكسجين، النترات، المواد الصلبة المعلّقة، العكارة، الفوسفات والعصيات الغائطية. تمّ تمثيل النتائج بيانيّاً وتمّت مقارنتها مع القيم المسموحة لمياه الشرب وفق المواصفة القياسيّة السوريّة لمياه الشرب رقم (2007) (45)، فتبيّن أنّ العديد من البارامترات قد تجاوزت الحدود المسموح بها في المواصفة، وصُنّفت مياه البحيرة وفق مؤشّر جودة المياه العالمي (NSFWQI)، وكانت من الدرجة(C) في مواقع العينات (S1-S2-S3) والوصف متوسط. أما في موقع العينة (S4) فصُنفّت من الدرجة (D) والوصف سيّئ، وبالتالي مياه البحيرة غيرصالحة للشرب وتحتاج إلى تنقية.